How Does One Learn? Is There a Method? - Hilcenko, Christine (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2020)
The definition of learning is to gain or acquire knowledge of or skill in (something) by study, experience, or being taught. We discuss here the different methods of learning in traditional and modern societies. We conclude that what we have learned to date is negligible compare to what remains to learn.